Framing Of Disability Representation in Story Books Chuskit Goes To School (2011) - Imelda Sari Manalu; Mutiara Balqista Nurazmi; Diva Dea Wildani; Hikmah Alya; Muhammad Yusuf (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study examines the representation of disability in the children’s storybook Chuskit Goes to School by Sujatha Padmanabhan. The study is grounded in the importance of children’s literature as a medium for shaping understanding of inclusion, educational rights, and acceptance of diversity. This research aims to describe how disability is framed in the story and how such framing contributes to the understanding of inclusive education. This study used a qualitative method with Gamson and Modigliani’s framing analysis model. The data consisted of dialogues, narratives, and visual elements related to disability, educational access, social responses, and Chuskit’s environment. The data were analyzed through framing devices and reasoning devices. The findings show that the story initially presents disability through limitation and exclusion, but gradually shifts toward an inclusive perspective by emphasizing Chuskit’s abilities, equal rights, and participation in education. The main barrier is not Chuskit’s physical condition, but an inaccessible environment. This study implies that the story reflects the social model of disability and presents inclusion as a shared responsibility.